Théoriser le genre : l'héritage de Beauvoir - Jackson, Stevi (Nouvelles Questions Féministes, 1999)
En déclarant qu' "on ne naît pas femme, on le devient", Simone de Beauvoir a posé les fondements d'une conception féministe du genre. L'analyse développée dans Le Deuxième sexe a anticipé la distinction ultérieure entre sexe et genre, et a également soulevé certains problèmes liés à cette distinction. Plutôt que l'oeuvre même de Beauvoir, ce sont les discussions récentes autour de la distinction sexe/genre qui font l'objet de cet article. Plus particulièrement, j'examine la manière dont les féministes matérialistes françaises, avec qui Beauvoir elle-même a travaillé, ont fait fructifier son héritage. En affirmant que le "sexe" est un phénomène tout aussi social que le "genre", ces féministes ont maintenu une tradition anti-essentialiste fondamentalement opposée aux perspectives "différentialistes" si souvent associées à la construction anglophone du "French feminism". Je confronte la contribution de ces féministes, notamment Christine Delphy et Monique Wittig, aux conceptions féministes du genre, avec l'approche plus déconstructive associée à des théoriciennes comme Judith Butler. Ce faisant, je plaide pour une analyse matérialiste du genre et pour une vision d'un monde sans genre plutôt que d'un monde avec de multiples genres. In claiming that 'one is not born, but rather becomes, a woman', Simone de Beauvoir laid the foundations for a feminist understanding of gender. The analysis developed in The Second Sex anticipated the later distinction between sex and gender, and also evinced some of the problems associated with that distinction. It is these more recent discussions of the sex/gender distinction which are the focus of this paper, rather than Beauvoir's work itself. More specifically, I consider the ways in which French materialist feminists, with whom Beauvoir herself worked, carry forward her legacy. In arguing that ' sex' is as much a social phenomenon as 'gender', these feminists have kept alive an anti-essentialist tradition which is fundamentally opposed to the 'difference' perspectives so often associated with the anglophone construction of ' French Feminism'. I compare the contribution that these feminists, especially Christine Delphy and Monique Wittig, have made to feminist understandings of gender with the more deconstructive approach associated with thinkers such as Judith Butler. In so doing I argue the case for a materialist analysis of gender and for a vision of a world without gender rather than a world with many genders.
Keywords: 1900-1999; approches et analyses; cours; discipline; fem1000; france; féminisme matérialiste; genre; histoire; histoire et politique; identités LGBTQIA2+; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; thématiques; théories féministes

Re-membering a Queer Body - Holmes, Morgan (UnderCurrents: Journal of Critical Environmental Studies, 1994)
In the spring 1993 issue of The Sciences, Brown University geneticist Anne Fausto-Sterling, citing the work of John Money, indicates that approximately four percent of the population is, to some degree, intersexual: they either possess physical characteristics of both officially recognized sexes or they have chromosomes which indicate a sex which are 'contradicted' by their physical appearance.1 In Toronto, the four percent figure translates into roughly 88,000 people. Yet little has been written about intersexuality, although its concerns often intersect with those of feminist and queer theory. This paper deals with feminist issues in patriarchal medicine and its relation(s) to intersexuality (and intersexuality's inherent ability to challenge arguments for the 'natural' basis of heterosexuality).
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme matérialiste; intersexuation; ontario; personnes intersexes; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2014; sociologie; thématiques; toronto; violences médicales

The Heterosexual Imaginary: Feminist Sociology and Theories of Gender - Ingraham, Chrys (Sociological Theory, 1994)
This essay argues that the material conditions of capitalist patriarchal societies are more integrally linked to institutionalized heterosexuality than they are to gender. Building on the critical strategies of early feminist sociology through the articulation of a materialist feminist theoretical framework, the author provides a critique of contemporary sex-gender theory. She argues that the heterosexual imaginary in feminist sociological theories of gender conceals the operation of heterosexuality in structuring gender and closes off any critical analysis of heterosexuality as an organizing institution.... every sociological concept and thesis, as well as the overall patterning of these concepts and theses, is potentially open for reconsideration... With the emergence of feminist sociological theory, the critical emphases in sociology are strengthened by an insistence that sociological work be critical and change-oriented... in an intensely reflexive way towards sociology itself (Lengermann and Niebrugge-Brantley 1990:318). We must produce a political transformation of the key concepts, that is of the concepts which are strategic for us (Wittig 1992:30).
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; féminisme matérialiste; histoire et politique; hétérosexisme; hétérosexualité; patriarcat; premier cycle; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques